Neighbor law : fences, trees, boundaries & noise (Nolo, 2025)
"Neighbor Law is more than a legal guide-it's a practical book filled with tips on how to solve problems and restore good neighbor relations. Readers can learn how to deal with noisy neighbors, trees that hang over a property line, blocked views, unclear boundary lines, high, unsightly, or deteriorating fences, dangers to children ("attractive nuisances"), problems with neighboring businesses, drones trespassing onto your property, and other common issues, like secondhand smoke, blighted property, and animal issues"--